Evaluation of Clinical Medicine in the Final Postgraduate Examinations in Family Medicine - Hanneke Dippenaar; Wilhelm J. Steinberg (South African Family Practice)
Background: The Family Medicine Department, University of the Free State (UFS) recently supervised the MFGP assessments of the College of Medicine in South Africa (first sitting), as well as the final assessment of the M Med Fam programme of the UFS (second sitting). The examinations, which took place in October and November 2006, were subjected to an internal quality assurance evaluation with the view to improve the standard and reliability of the examinations.